Country-level fire perimeter datasets (2001–2021) - Mahood, Adam L.; Lindrooth, Estelle J.; Cook, Maxwell C.; Balch, Jennifer K. (Scientific data, 2022)
Fire activity is changing across many areas of the globe. Understanding how social and ecological systems respond to fire is an important topic for the coming century. But many countries do not have accessible fire history data. There are several satellite-based products available as gridded data, but these can be difficult to access and use, and require significant computational resources and time to convert into a usable product for a specific area of interest. We developed an open source software package called Fire Event Delineation for python (FIREDpy) which automatically downloads and processes all of the source files for an area of interest from the MODIS burned area product, and runs a spatiotemporal flooding algorithm that converts those hundreds of grids into a single fire perimeter shapefile. Here we present a collection of fire event perimeter datasets for every country on the globe that we created using the FIREDpy software. We will continue to improve the efficiency and flexibility of the underlying algorithm, and intend to update these datasets annually. Measurement(s) Fire event occurrence • growth rate • size Technology Type(s) Satellite fire detections Sample Characteristic - Environment fire Sample Characteristic - Location global